2019
DOI: 10.1002/hed.25889
|View full text |Cite
|
Sign up to set email alerts
|

Tongue reconstruction: Rebuilding mobile three‐dimensional structures from immobile two‐dimensional substrates, a fresh cadaver study

Abstract: Objective To determine the two‐dimensional (2D) characteristics of flaps necessary to create three‐dimensional (3D) tongue anatomy. Methods Dissection of 11 fresh, nonpreserved human cadavers was performed. Six defects in each were created: total tongue, total oral tongue, hemiglossectomy, oral hemiglossectomy, total base of tongue, and hemi‐base of tongue. The resections were debulked to create flat, 2D mucosal flaps. The dimensions and shapes of these flaps were determined. Results Each specimen showed consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…As a result, oncological surgery with immediate reconstruction has the goal of restoring the shape and function of the resected parts beyond closing resection defects [9] . The tongue is one of the most challenging structures to properly reconstruct because glossectomy causes significant functional deficits due to the intricate tongue anatomy within a relatively small space [10][11] . Studies have shown that the effectiveness of current reconstructive efforts to restore tongue function directly affects patients' Quality of Life (QoL) and their ability to return to normal activities and interaction in society [12] .…”
Section: Discussionmentioning
confidence: 99%

Radial Forearm Free Flap for Tongue Reconstruction

Sánchez Terán,
Fuertes-Muñoz,
Gutiérrez-Brambila
et al. 2023
ijirms
“…As a result, oncological surgery with immediate reconstruction has the goal of restoring the shape and function of the resected parts beyond closing resection defects [9] . The tongue is one of the most challenging structures to properly reconstruct because glossectomy causes significant functional deficits due to the intricate tongue anatomy within a relatively small space [10][11] . Studies have shown that the effectiveness of current reconstructive efforts to restore tongue function directly affects patients' Quality of Life (QoL) and their ability to return to normal activities and interaction in society [12] .…”
Section: Discussionmentioning
confidence: 99%

Radial Forearm Free Flap for Tongue Reconstruction

Sánchez Terán,
Fuertes-Muñoz,
Gutiérrez-Brambila
et al. 2023
ijirms